The Paradox of Law Enforcement on Exoneration Clauses in Indonesia: A Critical Analysis of Mawardi's Fiqh Siyasah and Strict Liability Principle - Khoiruddin Manahan Siregar; Hendra Gunawan; Anwar Habibi Siregar (Madania: Jurnal Kajian Keislaman, 2025)
This study aims to examine the paradox of law enforcement regarding exemption clauses in Indonesia, strengthening the analysis from the perspective of fiqh siyasah (Islamic political jurisprudence) concerning the role of the state in guaranteeing substantive justice and protecting the rights of the mustadh'afin (consumers). The research critiques the inconsistency in judicial interpretation and the tension between the principle of contractual freedom and consumer protection, despite the Consumer Protection Law explicitly prohibiting businesses from exempting themselves from liability. Based on a comparison of pivotal court decisions, such as Decision Number 385/Pdt.G/2019/PN.Sby and Decision Number 334 PK/Pdt/2014, this normative legal research employs legislative, case, and conceptual approaches. The findings reveal that the strict liability principle—designed to strengthen consumers' bargaining position and eliminate the burden of proving fault—is often disregarded by judges who still adhere to classical principles from the Civil Code. From a fiqh siyasah perspective, this inconsistency reflects the state's failure (through the judiciary) to fulfill its duty as the protector of the people (ri'ayah) and the enforcer of public welfare (jalb al-mashalih), especially in addressing structural imbalances between businesses and consumers. Consequently, exemption clauses remain prevalent in sectors such as banking, transportation, insurance, and digital services. The study concludes that harmonizing judicial practices with consumer protection norms must be based on the principles of substantive justice and the state's moral responsibility (mas'uliyyah daulah) in preventing systemic injustice, which is the essence of siyasah syar'iyyah in regulating contractual relationships. Penelitian ini bertujuan untuk mengkaji paradoks penegakan hukum terhadap klausula eksonerasi di Indonesia, dengan memperkuat analisis dari perspektif fiqih siyasah mengenai peran negara dalam menjamin keadilan substantif dan melindungi hak-hak mustadh’afin (konsumen). Studi ini mengkritisi inkonsistensi penafsiran hakim dan ketegangan antara asas kebebasan berkontrak dan perlindungan konsumen, meskipun Undang-Undang Perlindungan Konsumen secara tegas melarang pelaku usaha membebaskan diri dari tanggung jawab. Berdasarkan perbandingan putusan-putusan penting, seperti Putusan Nomor 385/Pdt.G/2019/PN.Sby dan Putusan Nomor 334 PK/Pdt/2014, penelitian normatif dengan pendekatan perundang-undangan, kasus, dan konseptual ini menunjukkan bahwa prinsip strict liability—yang dirancang untuk memperkuat posisi konsumen—sering diabaikan oleh hakim yang masih berpegang pada asas klasik Kitab Undang-Undang Hukum Perdata. Dalam perspektif fiqih siyasah, inkonsistensi ini mencerminkan kegagalan negara (melalui kekuasaan kehakiman) dalam menjalankan tugasnya sebagai pelindung rakyat (ri’ayah) dan penegak kemaslahatan (jalb al-mashalih), terutama dalam mengatasi ketimpangan struktural antara pelaku usaha dan konsumen. Implikasinya, klausula eksonerasi tetap marak di sektor perbankan, transportasi, asuransi, dan layanan digital. Penelitian ini menyimpulkan bahwa harmonisasi antara praktik peradilan dan norma perlindungan konsumen harus didasarkan pada prinsip keadilan substantif serta tanggung jawab moral negara (mas'uliyyah daulah) dalam mencegah kedzaliman sistemik, sebagaimana menjadi esensi dari siyasah syar’iyyah dalam pengaturan hubungan kontraktual.